Prodigal son a novel - Steel, Danielle ([New York] : Random House Large Print, 2015)
"Fraternal twin brothers Peter and Michael McDowell have spent a lifetime competing for success and affection before that competition turned into an all-out war and made the brothers mortal enemies. While both Peter and Michael have grown into successful adults, they never managed to leave behind the animosity that took root in their childhood. With the collapse of his career and his marriage, Peter sees no other option than to move into the lake cottage his parents left him in their will--a place where he and Michael spent their summers and the only place that sparks pleasant memories of his childhood. It's there that Peter and Michael's lives intersect, as they begin to make peace with the past"--
102201
Keywords: Twins; Family secrets; Large type books